Endogenous Labor Market Insitutions in an Open Economy - Gabriel Felbermayr; Mario Larch; Lechthaler Wolfgang (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2011)
The paper sets up a two-country asymmetric trade model with heterogeneous firms,search frictions and endogenous labor market institutions. Countries are linked by tradein goods and non-cooperatively set unemployment benefits to maximize national welfare.We show that more open and smaller economies have more generous unemploymentbenefit replacement rates as a larger fraction of the costs is borne by foreign tradingpartners. These results are in line with empirical stylized facts. Additionally, we findthat the optimal level of unemployment benefits is independent from the level of unemploymentbenefits abroad and that non-cooperatively set unemployment rates areinefficiently high.
Keywords: F11; F12; F16; J64; L11; 330; Endogenous labor market institutions; unemployment; international trade; search frictions; heterogeneous firms; Arbeitslosenversicherung; Nichtkooperatives Spiel; Zwei-Länder-Modell; Außenwirtschaft; Offene Volkswirtschaft; Kleines-offenes-Land; Arbeitsuche; Theorie